Underestimation of endoscopic size in large gastric epithelial neoplasms - Jae Sun Song; Byung Sun Kim; Min A Yang; Young Jae Lee; Gum Mo Jung; Ji Woong Kim; Jin Woong Cho (Clinical Endoscopy, 2022)
Background/Aims Endoscopic submucosal dissection (ESD) is an effective method for resecting gastric adenomas and adenocarcinomas. A significant discrepancy was observed between endoscopic and pathological sizes in samples obtained from patients undergoing ESD. This study elucidates the factors affecting size discrepancy after formalin fixation. Methods The records of 64 patients with 69 lesions were analyzed, including 50 adenomas and 19 adenocarcinomas. Data on location, gross shape, histology, and size after fixation in formalin were collected. Results The mean size of the resected specimen appeared to decrease after formalin fixation (37.5 mm prefixation vs. 35.8 mm postfixation, p<0.05). The mean long axis diameter of the lesions was 20.3±7.9 mm prefixation and 13.4±7.9 mm postfixation. Size differences in lesions smaller than 20 mm were significantly greater than those in lesions larger than 20 mm (7.6±5.6 mm vs. 2.5±5.8 mm, p<0.01). In multivariate analysis, a tumor size of ≥20 mm was found to be an independent factor affecting size postformalin fixation (p<0.05). Conclusions The endoscopic size of lesions before ESD may be underestimated in tumors larger than 20 mm in size. Therefore, increased attention must be paid during ESD to avoid instances of incomplete resection.